The Sensitivity of Sag 1 and Bag 1 Probes to Detect Toxoplasma gondii in The Free-Rearing Chicken - Ida Ayu Pasti Apsari (Jurnal Sain Veteriner, 2012)
This study was aimed to determine the sensitivity of Sag1 and Bag1 Probe to detect in free-rearing chicken using dot blot hybridization method. Thirty serologically free-rearing chicken toxoplasmosis DNA were used as samples in this study. Sag1 and Bag1 probes were labeled by non-radioactive Dig-11-dUTP. The success of detection was based on the establishment of colored dot on the nylon membrane after detected with antibody-antiDig. The Sensitivity test of Sag1 and Bag1 probes in detection were conducted by making serial dilutions of the dot blot hybridization positive free-rearing chicken DNA. The results showed that 19 positive samples detected by Sag1 and Bag1 probe by dot blot hybridization method. The sensitivity of 5.87 pg / μl Bag1 probe to detect free-range chicken DNA was 0.23 ng / μl , and sensitivity of 6.72 pg / μl Sag1 Probe was 0.45 ng / μl. From the resuls above it can be concluded that the Bag1 probe was more sensitive than that of the Sag1 probe to detect Toxoplasma gondii of free-range chicken DNA.Keywords : Toxoplasma gondii; Sag1 and Bag1 Probe; Dig-11-dUTP; free-rearing chicken